2014
DOI: 10.1097/hp.0000000000000126
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Radiation Exposure in Relatives of Thyroid Cancer Patients Treated With 131I

Abstract: This work evaluates the radiological risk that patients treated with I for differentiated thyroid cancer could present to relatives and occupationally exposed workers. Recently, the International Atomic Energy Agency issued document K9010241, which recommends that patient discharge from the hospital must be based on the particular status of each patient. This work measures effective dose received by caregivers of patients treated with I at the Instituto Nacional de Cancerología, Mexico City. Thermoluminescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
1
3
0
2
Order By: Relevance
“…On this topic, the literature has an abundance of highquality studies which show that in almost all cases, the radiation dose to members of the patient's family is far less than whatever constraint is imposed. Similar studies have been conducted in the USA [3,4], Belgium [5,6] and Mexico [7]. In this series of studies which looked at the radiation dose to family members of thyroid cancer patients after radioactive iodine was administered, out of 219 family members who were monitored, only 14 (6%) exceeded the constraint of 1 mSv.…”
Section: Opening Statement-nicholas Forwoodsupporting
confidence: 60%
See 2 more Smart Citations
“…On this topic, the literature has an abundance of highquality studies which show that in almost all cases, the radiation dose to members of the patient's family is far less than whatever constraint is imposed. Similar studies have been conducted in the USA [3,4], Belgium [5,6] and Mexico [7]. In this series of studies which looked at the radiation dose to family members of thyroid cancer patients after radioactive iodine was administered, out of 219 family members who were monitored, only 14 (6%) exceeded the constraint of 1 mSv.…”
Section: Opening Statement-nicholas Forwoodsupporting
confidence: 60%
“…This would suggest that the hospitalisation protocol used by the institution was not the critical difference. Research has shown that the significant difference is between those who have excellent facilities for isolating at home and those who have very poor facilities for isolating at home [7,8]. In fact, when Iodine was administered as an outpatient procedure it was almost always possible to fit within the constraints required and this was especially the case in more developed countries [4,7].…”
Section: Opening Statement-nicholas Forwoodmentioning
confidence: 99%
See 1 more Smart Citation
“…El cáncer diferenciado de tiroides (CDT) es la enfermedad endocrina de diagnóstico más habitual (98%), 1 aunque es un tumor poco frecuente al representar un porcentaje muy pequeño del total de cánceres detectados a nivel mundial (< 1.5%). Las expectativas del paciente, tras un tratamiento adecuado, son excelentes alcanzando tasas de supervivencia del 97% a los 5 años.…”
Section: Introductionunclassified
“…Éste se encuentra en estado metaestable y se desexcita con la emisión de radiación gamma con energía 364 KeV. 1,4 La emisión de radiación gamma además del porcentaje de eliminación del radionúclido a través de la orina son las razones para tener que tomar medidas de protección radiológica tras la administración del radionucleido en la terapia metabólica. 5 Por ello, se ingresa al paciente en una habitación blindada con el WC conectado a un depósito especialmente preparado para recoger los excrementos en un área adecuada, lo que permite, además de la recogida controlada de la mayor parte del isotopo radiactivo eliminado por el paciente, la minimización de la exposición de los diferentes colectivos con riesgo de irradiación, particularmente el del personal sanitario y el del entorno más próximo al paciente.…”
Section: Introductionunclassified